Analysis of Medan State University Students' Perceptions of LGBT Deviant Behavior Viewed from an Islamic Religious Perspective - Hapni Laila Siregar; Almaida Harahap; Kanaka Wirasana Pradityo; Rezkya Nadilla Putri; Rinjani Vemilia; T.Sofia Chairani (International Journal of Education and Literature, 2024)
LGBT identities can emerge at any stage of life. However, adolescents, particularly university students who are in the process of self-discovery, are often more susceptible to this phenomenon. This research was designed to analyze student perceptions of LGBT behavior, with a focus on the Islamic religious perspective. The study employs quantitative descriptive research methods, conducted through the distribution of questionnaires to a sample consisting of student representatives from each faculty at Medan State University. Out of a total of 46 respondents, the majority stated that LGBT behavior is forbidden according to Islamic teachings. The respondents believe that the presence of LGBT individuals in the campus environment can influence Islamic values. Students suggest that the LGBT phenomenon requires special handling from an Islamic perspective. Students do not support initiatives aimed at providing protection for LGBT individuals. They feel the need to strengthen rules and regulations in their environment to prohibit activities or organizations related to LGBT.